NILAI SOSIAL-EKONOMI AIR DI KAWASAN PURA TIRTA EMPUL DESA MANUKAYA, KABUPATEN GIANYAR, BALI: SUATU PENDEKATAN EKONOMI LINGKUNGAN - SUDITA, MADE; ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 2 Juli 2006, 2012)
Government Rule of the Republic of Indonesia No. 82, 1991, article 7 section 2 concerning the Quality Management and the Control of Water Pollution stipulates that in planning the use of water, it is obligatory to pay attention to economic and ecological functions, religious values, and traditions that obtain in local community. This will bring an influence to the system of the flow of run off and infiltration that serve as the main source of the reserve of underground water supply The same is true for the flow of upper course of Tukad Pakerisan river which serves as the catchment's area has been under pressure so that it can influence the debit of water source in the area of Tirta Empul Temple. For this purpose, a study needs to be carried out in order to know the social benefit, total economic value, and the conservational effort that have been made by the community and the Regency Government of Gianyar. Through the study of environmental economy with the approach of total economic values, what will be obtained is direct and indirect use value, selection and heritage values, as well existence values. By knowing the water values in the area of Tirta Empul Temple will could account social benefit and total economic value. According the result and discussion, the social benefit of water within the area of Tirta Empul Temple is Rp. 782.199.620,00 per year and the total economic value of Rp 2.314.040.471,86 per year. Conservation effort that has been made by the community and the Regency Government of Gianyar such as the conservation of the forest that belongs to Laba Pura (the temple's area), the making of forest for the community, and the activities for making seeds for the local community. Based on that conclusion, it is suggested that in making the effort for the preservation of the function of the water within the area of Pura Tirta Empul that has important economic value so the development of catchment's area should be directed towards the area of yearly plants culturing.
Keywords: Social and Economic Value, Environment Economic, Sustainable Development.